Becoming frail: A more than human exploration. (May 2023) - Cluley, Victoria; Fox, Nick; Radnor, Zoe
'Frailty' is increasingly used as a clinical term to refer and respond to a particular bodily presentation, with numerous scores and measures to support its clinical determination. While these tools are typically quantitative in nature and based primarily on physical capacity, qualitative research has revealed that frailty is also associated with a range of social, economic and environmental factors. Here, we progress the understanding of frailty in older people via a new materialist synthesis of recent qualitative studies of frailty and ageing. We replace a conception of frailty as a bodily attribute with a relational understanding of a 'frailty assemblage'. Within this more-than-human assemblage, materialities establish the on-going 'becoming' of the frail body. What clinicians refer to as 'frailty' is one becoming among many, produced during the daily activities and interactions of older people. Acknowledging the complexity of these more-than-human becomings is essential to make sense of frailty, and how to support and enhance the lives of frail older people.